Understanding and improving sustainable use of coral reef resources - Arghya Mandal; Mainak Banerjee (Academia Environmental Sciences and Sustainability)
Coral reefs harbor an unparalleled biodiversity and provide critical ecosystem services to millions of people worldwide. However, unsustainable fishing, pollution, habitat degradation, and climate change pose tremendous risks to these priceless ecosystems. For the sake of maintaining these ecosystems and the lifestyles they sustain, it is essential to comprehend and enhance the sustainable use of coral reef resources. We integrate ecological, social, and economic information to better understand sustainable coral reef resource utilization. We draw attention to the intricate relationship that exists between human activity and the health of coral reefs, highlighting the necessity of holistic management strategies that take socioeconomic development and ecological preservation into account. The relevance of legislative frameworks in encouraging sustainable behaviors is complemented by the role of technology and innovation in monitoring and conservation efforts. In addition, this review addresses new issues, including ocean acidification and climate change’s effects, as well as programs for reef restoration and nature-based remedies that could improve reef resilience. This review outlines viable paths for improving the sustainable utilization of coral reef resources by referencing case studies from various geographical areas. It emphasizes the value of long-term investments in conservation and restoration projects, interdisciplinary cooperation, and adaptive management techniques. Through the integration of scientific knowledge with traditional ecological knowledge and local skills, stakeholders may collaborate to protect these priceless ecosystems and preserve them for future generations.